Chiroptical amplification of [7]-helicene nanographene by additional helical chirality - Dongre, Sangram D.; Venugopal, Geethu; Kumar, Viksit; Badrinarayan Jadhav, Ashok; Kumar, Jatish; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2025)
Nanographenes have captivated scientific interest since the pioneering discovery of graphene. Recently, attention has shifted towards exploring chiral and nonplanar nanographenes, for their distinct optical, chiroptical, and electronic properties. Despite the growing acceptance of helicenes, the research on inducing helical chirality on pi-extended derivatives to boost chiroptical properties remains unattended. In our study, we introduce a new pi-extended [7]-helicene resulting from the condensation of diamines with 3,6-dibromophenanthrene-9,10-dione, complemented by two hexabenzocoronene arms in the periphery. Notably, the nanographene containing binaphtho-[1,4]diazocine, compared to the corresponding phenazine, exhibits a remarkable average 2.5, 5, and 10-fold enhancements in quantum yield, dissymmetry factor, and brightness, respectively, when measured in five different solvents. These improvements underscore the significance of the induced helical chirality by the antiaromatic binaphtho-[1,4]diazocine in influencing the chiroptical properties of the helical nanographene. Our research represents a significant stride toward unlocking the potential of pi-extended helicenes and lays the groundwork for further exploration in designing and synthesizing new chiral nanomaterials.
Keywords: circularly polarised luminescence; dissymmetry factor; helicene; nanographene; quantum yield